Georgios Deligiannakis, A Cultural History of Late Roman Cyprus - Winther-Jacobsen, Kristina (Journal of Greek Archaeology, 2024)
The title of A Cultural History of Late Roman Cyprus does not do justice to its content. The cultural element is dominated by religious questions. The introduction places the book among the work of historians, and the study draws largely on written sources and epigraphy, but also on archaeological evidence. The book discusses specifically the period from the reign of the emperor Diocletian (283-305) to the year 431 when the Church of Cyprus was granted the status of autocephaly. Finally, the analyses place the study of the island firmly in its wider Eastern Mediterranean context.